The application of blockchain to the chain of custody of judicial evidence - Parra de Gallo, Herminia Beatriz; Medina, Oscar Carlos; Dorado, Jhon Grover; Aráoz Fleming, José; Notario, Enzo; Sánchez, Ernesto; Párraga, Carlos (My University, 2020)
This article explores the application of Blockchain technology to the Chain of Custody of Judicial Evidence. The admissibility of evidence –considering the integrity, confidentiality, and reliability of an item of evidence in a trial– is fundamentally important to administer justice. The objective set in this paper is to define an architectural model for the implementation of smart contracts for the safe recording of the Chain of Custody of Judicial Evidence, taking advantage of the traceability and security features of Blockchain technology, and avoiding the risks of non-admissibility of evidence to which the current Chain of Custody Records are exposed. The conceptual model is described, but the implementation of this methodology is still being developed.
Keywords: Blockchain; Chain of custody; Judicial evidence; Smart contract; Traceability